Pre-service Teachers’ Intercultural Learning through the SEA Teacher Program: A Qualitative Study in Vietnam - Hana, Laela; Ardini, Sukma Nur; Widiyanto, Muhammad Wahyu (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
This research investigated the cultural immersion and pedagogical exchange of pre-service teachers participating in the SEA Teacher program, with focus on its impact on teaching practices and career development in the home country. A phenomenological qualitative design was employed. Data were collected through questionnaires and interviews with twelve pre-service teachers who participated in the SEA Teacher program in Dong Thap, Vietnam. Therefore, the criteria taken in the selection of participants such as: (1) participation in the full duration of the program, (2) teaching experience in at least one host school in Dong Thap, and (3) willingness to engage in in-depth interviews and reflection. Participants reported increased awareness of the need to adapt teaching methodologies to align with local cultural contexts, which was perceived to improve learning outcomes and foster cultural sensitivity. Language barriers were reframed as opportunities to employ creative instructional strategies, such as games and collaborative activities, which enhanced student engagement. The research also highlighted the role of cultural knowledge, communication skills, and open-mindedness in promoting inclusive learning environments. Findings suggest that integrating culturally responsive pedagogies contributes to a positive and engaging classroom atmosphere. Furthermore, this research identified a need for structured pre-program training, including virtual classroom observations and curriculum workshops with partner institutions. The participants’ readiness may be enhanced with such preparation to design context-specific learning modules and navigate local educational systems effectively.